1992
DOI: 10.1021/ja00047a005
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and structure of modified uridine dinucleosides are determined by thiolation

Abstract: 7989 essential imidazolium to the unstable tetrahedral intermediates produced from amides where the N is an aliphatic one, the proton transfer is thermodynamically favorable, and in the case of anilides is either thermodynamically neutral or only slightly uphill.The second and less obvious feature of imidazole which makes it unusually suitable for general-acid or -base catalysis relative to an aliphatic amine (ammonium) has to do with the molecular shape. Because the proton transfer in imidazole occurs at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 4 publications
0
39
0
Order By: Relevance
“… Calculated from coupling constants ( J 4′5′ / J 4′5″ ) by the formula % γ = [((13.75 − J 4′5′ − J 4′5″ )/10.05) × 100] from the NMR experimental data …”
Section: Resultsmentioning
confidence: 99%
“… Calculated from coupling constants ( J 4′5′ / J 4′5″ ) by the formula % γ = [((13.75 − J 4′5′ − J 4′5″ )/10.05) × 100] from the NMR experimental data …”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate that this could be achieved selectivity through thermodynamic stabilization of the wobble base pair by modified bases. The modified nucleotide and its base-pairing affect the stability of the adjacent nucleotide conformation and its base pairs (Smith et al 1992;Testa et al 1999); and, thereby, it affects the overall stability of an entire RNA, or the mini-helix of the anti-codon-codon interaction (Smith et al 1992;Kumar and Davis 1997;Testa et al 1999;Sipa et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…7,56 The s 2 , and not the 5-position modification, produces the significantly more stable, anti C3'-endo, g + conformation, and transfers a similar restraint to the 3'-neighbor. 57 In studies of ASLs, it has been demonstrated that mcm 5 U 34 has little measurable effect on structure, but that s 2 U 34 increases the amount of stacking between U 34 and U 35 . 41 This is evident when comparing the anticodon structure of the A-site hASL Lys3 UUU -mnm 5 U 34 ;t 6 A 37 with that of the hASL Lys3 UUU -mcm 5 s 2 U 34 ,ms 2 t 6 A 37 ψ 39 (Fig.…”
Section: Crystal Structures Of the Hasl Lys3 Uuu Interaction With Mrnmentioning
confidence: 99%